Principal Leadership in Decision Making in Educational Institutions - Hotmaida Sidabutar; Taufiq Ramadhani; Saut Purba; Irsan Rangkuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to describe the principal's leadership role in decision making, the process of making decisions by the principal, as well as the factors that support the principal's leadership role in decision making. This study uses a qualitative approach. The data sources used in this study were school principals, teachers and education staff. Analysis of the data used in this study through data reduction, data display, and data verification. The results of this study are (a) the role of the principal in the role of the decision-making process, namely the role of regulatory, democratic, and persuasive; (b) the decision-making process carried out by the principal, namely holding workshops, identifying problems, alternative problem solving, determination of the selected alternative and decision making; (c) factors that support the leadership of the school principal in making decisions, namely all parties are open to the problems faced by the school and provide freedom of opinion in making decisions.